Adsorption characteristics of various MOF adsorbents plus CO2 systems - Chua, Vivian Ying Qi (2018)
Over the past few years, there is a continuous increase of greenhouse gases in our atmosphere. Excessive carbon dioxide (CO2) in the atmosphere is a problem that the world is currently facing. The effects on the environment caused by human have exceeded what the nature can regenerate. Hence, various measures have been implemented to reduce CO2 emissions. One such measures included is Carbon Capture and Storage (CCS). It is a process of capturing waste CO2 and storing it underground. Metal Organic Frameworks (MOFs) are widely used in CCS due to its porous structure and wide array of potential applications. Thus, the project seeks to investigate the porous characteristics of the various adsorbents and to determine which adsorbent have a better adsorption capacity. In this report, three MOFs were studied with experimental pressure limited to 10 bars and at temperatures ranging from 220K to 300K, using a volumetric and cryogenic set-up. The three MOFs are HKUST SAMPLE 1, HKUST SAMPE 2 and HKUST-1 with 50mg MAXSORB III (Activated Carbon). BET theory, XRD and SEM methods are used to analysed the physical properties of the material; such as the pore structures, surface area and pore volume. Based on the experimental results acquired, it has been observed that the adsorption capabilities are better at lower temperatures. HKUST SAMPLE 2 have the highest gravimetric uptake. After testing different samples of HKUST of different synthesis adsorbent, at varying temperature and pressure, a fitted curve is derived using the Sun- Chakraborty isotherm model. By applying the Clausius-Clapeyron equation, the isosteric heat of adsorption (Q!") is obtained, which shows a decreasing trend as the gravimetric adsorption is increased. Since HKUST SAMPLE 2 have the highest gravimetric and volumetric uptake instead of MAXSORB III-assisted HKUST-1, further studies should be done to synthesise the best MOF to enhance the adsorption uptake of carbon dioxide on MOFs.